(untitled) (Journal of Bangladesh Academy of Sciences, 2014)
The chloroform and methanol extracts of seed and seed coat of Caesalpinia bonduc L., Mucuna pruriens L., Adenanthera pavonina L., Terminalia bellirica Geatn., Syzygium cumini L. and Myristica fragrans Houtt. were tested against 14 pathogenic bacteria. According to the intensity of activity against the selected bacteria the extracts could be arranged in a descending order of M. fragrans > A. pavonina > S. cumini > C. bonduc > M. pruriens > T. dbelerica. The minimum inhibitory concentrations (MIC) of the chloroform extract of seed of Syzygium cumini were 128 ?g/ml against Bacillus cereus and 64 ?g/ml against S. aureus. For the methanol extract the MIC values were 128 ?g/ml against B. cereus, Shigella dysenteriae and 64 ?g/ml against B. megaterium, S. aureus and S. sonnei. DOI: http://dx.doi.org/10.3329/jbas.v38i2.21335 Journal of Bangladesh Academy of Sciences, Vol. 38, No. 2, 119-125, 2014